Appendiceal Crohn's disease: a rare differential of right iliac fossa pain. Issue 2 (28th February 2020) - Crellin, Adam James; Musbahi, Omar; Onwu, Natasha; Singh, Sandeep
Abstract : A 30-year-old man with a history of severe right iliac fossa pain was referred to the surgical emergency unit. His symptoms began 3 days prior as mild, non-specific abdominal pain which progressively localised to the right iliac fossa and worsened in severity. Investigations were suggestive of acute appendicitis, and therefore a laparoscopic appendicectomy was planned. Laparoscopy revealed a thickened, necrotic appendix with a mass at the base of the appendix, in keeping with the appearance of an appendiceal malignancy. Subsequently a right hemicolectomy was performed. Histology revealed active chronic inflammation and granulomas highly suggestive of appendiceal Crohn's disease. Since, the patient has made a good recovery and presently shows no further signs of Crohn's disease. This case is demonstrative of one of many rare findings on histological examination of the appendix. It emphasises the need for a wide differential when investigating right iliac fossa pain.